2020
DOI: 10.1016/j.drugalcdep.2020.108215
|View full text |Cite
|
Sign up to set email alerts
|

High-dose adolescent nicotine exposure permits spontaneous nicotine self-administration in adult male rats

Abstract: Introduction: While cigarette smoking rates have been steadily decreasing over the past decade, there has been a dramatic increase in nicotine use via e-cigarettes, especially during adolescence. Adolescent e-cigarette use is associated with a greater risk of future cigarette smoking, and increased rates of cigarette smoking in individuals who may have otherwise never tried cigarettes. In humans and rodents, early initiation of nicotine use has been associated with greater consumption, dependence, and persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There is evidence that nicotine injection during adolescence alters responses in rats during adulthood. For example, Renda and colleagues found that male rats treated with nicotine (1.0 mg/kg, s.c.) once daily from Post-Natal Day (PND 28-41) did not intravenously self-administer more nicotine as adults under initial Fixed Ratio (FR1) or a Progressive Ratio contingency, but did self-administer slightly more under a Fixed-Interval 1 minute procedure (Renda et al, 2020). Cardenas and Lotfipour (Cardenas and Lotfipour, 2022) reported increased self-administration of methamphetamine in male rats treated with nicotine by i.v.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that nicotine injection during adolescence alters responses in rats during adulthood. For example, Renda and colleagues found that male rats treated with nicotine (1.0 mg/kg, s.c.) once daily from Post-Natal Day (PND 28-41) did not intravenously self-administer more nicotine as adults under initial Fixed Ratio (FR1) or a Progressive Ratio contingency, but did self-administer slightly more under a Fixed-Interval 1 minute procedure (Renda et al, 2020). Cardenas and Lotfipour (Cardenas and Lotfipour, 2022) reported increased self-administration of methamphetamine in male rats treated with nicotine by i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine exposure during a development period analogous to adolescence enhances self-administration and conditioned place preference (Adriani et al, 2002;Vastola et al, 2002). Similar studies have found that exposure to nicotine in adolescence, when compared to later developmental periods, significantly increased motivation to work for nicotine self-administration (Adriani et al, 2003;Renda et al, 2020).…”
Section: Introductionmentioning
confidence: 66%
“…However, it is difficult to track individual differences in consumption when animals share a cage and a common substance source. The majority of drug intake studies in rodents have required social isolation of subjects to get around this issue, neglecting the social context so relevant to clinical populations [2,11]. Radio frequency tracking is one promising solution and has been used in commercial products such as IntelliCage.…”
Section: Introductionmentioning
confidence: 99%